Economic valuation of the Emas waterfall, Mogi-Guaçu River, SP, Brazil - Peixer,Janice (2011)
The Emas waterfall in Mogi-Guaçu River is regionally recognized as an important fishing spot and touristic place. The first reports of the professional and sport fishing there date back from the 30's, which is the same period when the tourism took place. The present paper provides an environmental valuation of this place and an assessment of the differences among the major groups of people using the area. During 2006 we interviewed 33 professional fishers, 107 sport fishers, 45 tourists and 103 excursionists in order to estimate the Willingness to Pay (WTP) for each category and to analyze the influence of socioeconomic factors by means of logistic regressions and ANCOVAs. The WTP of professional fisher was significantly influenced by age and education, and the WTP for the sport fishers was influenced by the family income. The variables that influenced the tourists' and excursionists' WTP were sex and education. The total annual aggregated value to maintain the waterfall in the current conditions was estimated in US$ 11.432.128, and US$ 55.424.283 to restore it.